SOLESEVANA : THE ROLES OF LOCAL SCHOLARS IN TRANSFERRING LOCAL WISDOM TO STRENGTHEN COMMUNITIES - Sanannaree, Nites; Phengwiphat, Phonphao; Buathed, Decha; Leeka, Jaras; Maleewong, Panithan (Journal of Graduate MCU KhonKaen Campus, 2020)
This research article is a part of the research on SOLESEVANA : Local Scholars as the Roles of Informal Leaders for Local Wisdom Socialization to Strengthen Community. The aim was study the roles of local scholars in transferring local wisdom to strengthen communities. The present study was in line with that of the Qualitative Method integrated with documentary ,focus group discussion and indept-interview method. The population and the targeted group of this research were purposesively selected consisted of local scholars ,local leaders, Community leaders , monks, government representatives , Students and people with the grand amount of 80 people Included with 2 network partners in Khon Kaen province totaling 80 people and 2 networks. The research tools in this regard were that of focus group discussion form and in-depth interview form. The collected data were analyzed in favor of Descriptive Analysis in accordance with inductive method. The Research findings in the roles of local scholars in transferring local wisdom to strengthen communities was found that there were 6 main points : (1) cultural leadership of the community (2) being a knowledge treasery base in society (3) transfer of knowledge to the community (4) problem solving with wisdom ( 5) creating innovations and (6) creating networks